The Power of Principal Leadership in Boosting School Quality - Purhasanah, Siti (Munaddhomah: Jurnal Manajemen Pendidikan Islam, 2024)
This study investigates how the principal's leadership affects school quality improvement. The research was conducted at MI Al-Ikhlas Cikawung using a quantitative approach, involving survey methods and correlation analysis. The participants included teachers and administrators from the school and Islamic boarding schools, with a sample size of 31 people. Data collection involved questionnaires and interviews, both of which were found to be valid and reliable. The normality of the data was assessed using the Kolmogorov-Smirnov test. The findings indicate a very strong relationship between the principal's leadership and the quality of education at MI Al-Ikhlas Cikawung, with a correlation coefficient of 0.907. The analysis revealed that the principal's leadership explains 81.2% of the variation in educational quality, while the remaining 18.8% is attributed to external factors, as shown by the regression equation model Y = 18.12 + 0.66X. Future studies might explore differences, correlations, and interactions in student learning outcomes based on cognitive stages and gender and compare these results with those of other schools.